Alpha-fetoprotein and carbohydrate antigen 19-9 as prognostic biomarkers in acute liver failure: A retrospective study - Rui Qi; Xin Wang; Zhidan Kuang; Xueyi Shang; Fang Lin; Dan Chang; Jinsong Mu (Journal of International Medical Research)
Objective To investigate the clinical significance of alpha-fetoprotein and carbohydrate antigen 19-9 as potential predictors of outcomes in patients with acute liver failure. Methods We conducted a retrospective analysis of 208 patients with acute liver failure admitted to the intensive care unit between 2009 and 2023. Serum alpha-fetoprotein and carbohydrate antigen 19-9 levels were measured on Days 1 and 3, and their prognostic value was evaluated using logistic regression and receiver operating characteristic curve analyses. Patients were stratified by etiologies to assess biomarker performance across different causes of acute liver failure. Results Nonsurvivors had significantly lower alpha-fetoprotein levels and higher carbohydrate antigen 19-9 levels than survivors on Days 1 and 3 (all p  <   0.05). Alpha-fetoprotein levels increased over time in both groups, whereas carbohydrate antigen 19-9 levels increased in nonsurvivors and decreased in survivors. The combination of carbohydrate antigen 19-9 with the Model for End-Stage Liver Disease score significantly improved prognostic accuracy, with an area under the curve value of 0.828, compared with 0.784 for alpha-fetoprotein combined with Model for End-Stage Liver Disease score. Etiology-specific analysis revealed that carbohydrate antigen 19-9 showed the best predictive performance in acetaminophen-induced acute liver failure (area under the curve value = 0.885), whereas alpha-fetoprotein showed better predictive performance in viral hepatitis-associated acute liver failure (area under the curve value = 0.880). Conclusions Alpha-fetoprotein is a protective prognostic factor, whereas carbohydrate antigen 19-9 enhances outcome prediction, particularly when combined with Model for End-Stage Liver Disease score. Etiology-specific biomarker performance supports tailored prognostic approaches in the management of acute liver failure.